Expert consensus on the management process of gynecological emergency under the regular epidemic prevention and control of COVID-19 - Hongbo Wang; Wei Zhang; Xin Du; Yan Kuang; Xiaomao Li; Xiaoxin Ma; Lan Xiao; Xiaojun Chen; Yu Zhang; Donglin Li; Lang Zheng; Yanhui Li; et al. (BMJ Publishing Group, 2021)
At present, China is in the stage of the COVID-19 epidemic where regular prevention and control measures are required to contain the spread of disease. Reports of new sporadic cases are still widespread across China and medical personnel remain at high risk of exposure to infection. This is especially the case for medical staff working within emergency departments. Most gynecological emergency cases are complex and a high proportion require emergency surgical treatment. By referring to national regulations and requirements on COVID-19 prevention and control, and by summarizing our experiences in the battle against COVID-19 within Wuhan, this consensus report provides recommendations on the triage, reception, consultation, admission and surgical management of gynecological emergency patients. We also make suggestions for the environmental layout and disinfection and the medical waste management. This consensus aims to optimize the diagnosis and treatment process of gynecological emergency patients and reduce the exposure risk of medical staff within the current context of routine COVID-19 prevention and control.